The administration of multipotent stromal cells at precancerous stage precludes tumor growth and epithelial dedifferentiation of oral squamous cell carcinoma - Bruna, Flavia Alejandra (2017)
Multipotent stromal cells (MSCs) are envisioned as a powerful therapeutic tool. As they home into tumors, secrete trophic and vasculogenic factors, and suppress immune response their role in carcinogenesis is a matter of controversy. Worldwide oral squamous cell carcinoma (OSCC) is the fifth most common epithelial cancer. Our aim was to determine whether MSC administration at precancerous stage modifies the natural progression of OSCC. OSCC was induced in Syrian hamsters by topical application of DMBA in the buccal pouch. At papilloma stage, the vehicle or 3 × 106 allogenic bone marrow-derived MSCs were locally administered. Four weeks later, the lesions were studied according to: volume, stratification (histology), proliferation (Ki-67), apoptosis (Caspase 3 cleaved), vasculature (ASMA), inflammation (Leukocyte infiltrate), differentiation (CK1 and CK4) and gene expression profile (mRNA). Tumors found in individuals that received MSCs were smaller than those presented in the vehicle group (87 ± 80 versus 54 ± 62 mm3, p < 0.05). The rate of proliferation was two times lower and the apoptosis was 2.5 times higher in lesions treated with MSCs than in untreated ones. While the laters presented dedifferentiated cells, the former maintained differentiated cells (cytokeratin and gene expression profile similar to normal tissue). Thus, MSC administration at papilloma stage precludes tumor growth and epithelial dedifferentiation of OSCC.